2022
DOI: 10.3389/fpsyt.2022.814360
|View full text |Cite
|
Sign up to set email alerts
|

The Global Landscape of the Burden of Depressive Symptoms/Major Depression in Individuals Living With HIV/AIDs and Its Effect on Antiretroviral Medication Adherence: An Umbrella Review

Abstract: BackgroundPeople living with HIV/AIDS have a higher rate of depression/depressive symptoms and this highly affects antiretroviral medication adherence. Therefore, much stronger evidence weighing the burden of depressive symptoms/major depression is warranted.MethodsWe investigated PubMed, Scopus, Psych-Info, and Embase databases for systematic review studies. A PRISMA flow diagram was used to show the search process. We also used the Assessment of Multiple Systematic Reviews (AMSTAR) checklist scores. A narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…A substantial body of research documents the negative association between depression and HIV care continuum outcomes. Depression has been associated with increased odds of lower antiretroviral a therapy (ART) use or poorer adherence [8][9][10][11] and poorer retention in HIV care [12]. Longitudinal studies demonstrate the harmful impact of depression over time.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of research documents the negative association between depression and HIV care continuum outcomes. Depression has been associated with increased odds of lower antiretroviral a therapy (ART) use or poorer adherence [8][9][10][11] and poorer retention in HIV care [12]. Longitudinal studies demonstrate the harmful impact of depression over time.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is the most common neuropsychiatric disorder among PLWH. Depression results in poor physical health [ 4 ], reduced ART adherence [ 5 7 ], treatment failure [ 8 ], reduced quality of life [ 9 , 10 ], increased suicidal behaviours [ 11 , 12 ] and HIV-related mortality among PLWH [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated global prevalence of depressive symptoms among PLWHA is 34.17%. 8 A systematic and meta-analysis study reports the prevalence of depressive symptoms using screening tool to be 26.0% in sub-Saharan Africa, and 44.7% in South Africa, respectively. 9 In addition, the prevalence of depressive symptoms among HIV-positive individuals in sub-Saharan Africa was 27.0% with a mean estimate of 6.376 million, while in South Africa it was 29.1% with a mean estimate of 2.076 million.…”
Section: Introductionmentioning
confidence: 99%
“…18,24,27 Yet, research has shown that HIV-related clinical variables associated with depressive symptoms in PLWHA include side effects of ART, [28][29][30] and poor adherence to ART. 1,8,13,15 Depressive symptoms are detrimental to the health of PLWHA, particularly when adherence to ART is irregular. A recent study found that PLWHA with depressive symptoms were 2.6 times more likely to not adhere to their ART medication than their counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation